Effect of Silver Nanoparticles on the Mechanical and Physical Properties of Epoxy Based Silane Coupling Agent - Vengadaesvaran, B.; Arun, N.; Chanthiriga, R.; Bushroa, A.R.; Rau, S.R.; Ramesh, K.; Al-Shabeeb, G.H.E.; Ramesh, S.; Arof, Abdul Kariem (Trans Tech Publications, 2014)
In this work, silver nanoparticles were synthesized using the precipitation method at room temperature. The size of the silver nanoparticle was analyzed using transmission electron microscope and found to be in the range of 20 to 40 nm. The multi-functional transparent film on glass substrate was prepared using silver nanoparticle solutions and 3-Glycidyloxypropyltrimethoxy silane (GLYMO) by dip coating method. Ultraviolet visible spectroscopy measurement shows low absorbance thus confirming high transparency level. The critical load obtained from the micro-scratch test showed an increase from 3000 mN to 3319 mN.